COVID-19 VACCINATION TABOO: EARLY VACCINATION TO PREVENT SEVERE DISEASE IN THE ELDERLY A MYTH? - Y. X. Liew; T. Thong (Asian Journal of Medicine & Health Sciences, 2021)
The Coronavirus disease 2019 (COVID-19) outbreak has become a global pandemic infecting millions of people globally, causing disabilities and significant loss of life, especially in the elderly population due to their greater susceptibility towards the debilitating infection leading to further complications. Thus, various vaccination program is underway to protect them against COVID19. This case report of two elderly patients with comorbid who were infected with COVID-19 post-vaccination aims to showcase the importance of early vaccination to prevent severe disease and complications of COVID-19. Despite contracting the disease, both patients were asymptomatic and did not suffer any complications of COVID-19, providing evidence of the impact of early vaccination has on preventing complications in the elderly.